Correlational study of Vitamin-D deficiency levels and its severity of community-acquired pneumonia in patients admitted into a tertiary care hospital - M, Sai Varun; Mudipalli, Deepthi (Journal of Applied Pharmaceutical Research, 2024)
Background: Recent studies have emphasized that people who have low levels of Vitamin D are more prone to the development of infectious diseases, particularly of a community-acquired nature, which has differential morbidity and mortality. Aims & objectives: The present study aimed to determine the correlation between different levels of vitamin D deficiency and severity and outcomes in patients diagnosed with community-acquired pneumonia. Methods: In this study, the serum level of Vitamin D of 100 consecutively admitted community-acquired pneumonia patients was measured. Depending on the level of Vitamin D deficiency, patients diagnosed with community-acquired pneumonia (CAP) were assessed for severity of illness by CURB-65 score. Results & Discussion: In the study population, out of 100 patients, 82% of the study sample had deficient serum vitamin D levels. In the study sample, 41 patients with higher deficiency levels of serum Vitamin D have severe illness and scored high on CURB- 65, which is in the range of three to four on the scale. 59 patients with low deficiency levels of serum Vitamin D had low scores of one or two on the CURB-65. On severity assessment in patients with severe deficiency of Vitamin D, the mean length of hospital admission was 12.30±8.47 days compared to patients with mild deficiency of Vitamin D, where the average hospital stay was 8.58±4.04 days. Conclusion: As the severity of deficiency of Vitamin D increases, the frequency of CAP increases, and it is also observed that a severe degree of deficiency is associated with severe illness and prolonged hospital stay.